the Restorative Justice in Action; the Kalinga Experience: Restorative Justice in Action; the Kalinga Experience - garcia, mario (IJRDO - Journal of Social Science and Humanities Research, 2019)
Restorative justice as practiced in Kalinga is very evident in all aspects, from the barangay, the community, the tribes, Academe and the regular courts to include the churches.Restorative justice in its concept is respecting the rights of persons involved in a conflict to settle by them that may lead to the restoration of their broken relationships caused by disputes.In Kalinga, the different groups were empirically solicited with their restorative practices in their respective jurisdictions like;Which involved the law enforcement, the barangay officials and the MBCC as subgroups of respondents representing the community. It is very evident that these groups are instrumental in restoring disputes by way of giving reservations to the rights of the parties in the restoration of their differences.The court as the second set of respondents, the city court was purposively selected as representative of the regular justice system. With the MTC as representative of the court, it was found out that it also considers the settlement of both parties on a dispute as a ground for dismissal or deciding a case.Under this area, three levels of academic institutions were considered as institutional respondents of the study. Elementary, secondary and the tertiary level, it is also revealed on the process that several processes of settling disputes between students, faculty and administration were observed and that all leads to a peaceful resolution.Theology/Religion/church. The two umbrella religions were being considered, the Islam and Christian religion. It is found out that the common conflict between these two religions is their belief on the personality of Jesus and whether or not pig meat is edible. Conflicts are not limited to the two umbrella religion but also internal conflicts within the same religion exist. But despite all these conflicts, religious groups always settled to the idea of dialogue rather than debate or argument.